Key Technology of Automatic Analysis of Fault Area Wave Recording of Power System - Yuanbo YE; Xiaoping CHENG; Zhaoyun ZHANG; Hongjun LIU; Wei WANG; Qingzhu SHAO (Zhongguo dianli)
In this paper, an automatic analysis method of power system fault recording is proposed and developed. It is an important part of relay protection real-time evaluation system based on wide area information. Through the use of automatic analysis system, the efficiency and quality of power system fault recording analysis are greatly improved, and the labor cost is greatly reduced, which greatly reduces the time of fault analysis and improves the quality of fault analysis. The system has been trial run in a power dispatching center. The operation results show that the scheme has good feasibility and effectively improves the maintenance efficiency of operation and maintenance personnel.